Multiple Linear Regression Model to Measure the Influence of Gold Price Fluctuations and Promotions on Customer Interest in Gold Installment Products - Putri Ridhotul Uliyah; Sri Idayana (Jurnal Inotera, 2025)
This study aims to determine the effect of gold price fluctuations and promotions on customer interest in using gold installment products at PT. Pegadaian UPS Johan Pahlawan. The population in this study were customers of PT Pegadaian UPS Johan Pahlawan. The sample in this study amounted to 61 respondents. The technique used in this test is Multiple Linear Regression Analysis. The model used in this research is descriptive quantitative. data analysis was carried out using the help of SPSS version 25. With a sig value of 0.000 <0.05, the Fhitung value is 25.766> Ftabel 3.16. So gold price fluctuations and promotions, simultaneously, have a positive and significant influence on customer interest. in the first regression equation obtained a Rsquare value of 0.470 or 47.0%. So it can be concluded that at PT Pegadaian UPS Johan Pahlawan, gold price fluctuations and promotions simultaneously have a positive effect on customer interest in using gold installment products.